Effect of design parameters on the performance of a new modified annular TEG system - Karana D.R.; Sahoo R.R. (My University, 2025)
The present study deals with the design and development of a new modified annular TEG (MATEG), in which heat transfer takes place along the longitudinal direction. Such type of geometric arrangement can be useful extremely in fluid-carrying bend pipes. Also, such types of designed thermoelectric generators (TEGs) are applicable for round-shaped heat sinks and source, where the performance suffers due to the mismatch of geometries. By using the governing equations, a steady-state theoretical model has been developed to predict the performance of the proposed MATEG system. The new model is simulated with parallel flow and counterflow cooling configurations. Moreover, the effects of a number of TEG modules, geometric dimensions, angle ratio, length of the module, total angle, and of the height of junction on the performance are investigated. The results reveal that maximum power is obtained for the present model MATEG system with five numbers of the module and increasing length of TEG module, the power density decreases with slight fluctuation in the conversion efficiency. In the present analysis, the new geometry has a strong effect on these performance parameters. This new MATEG system is also applicable to both the U-type and L-type bends. © 2019 by Begell House, Inc.